State Oversight of Nonprofit Governance: Confronting the Challenge of Mission Adherence Within a Multi-dimensional Standard - Blodgett, Mark S.; Melconian, Linda J.; Peterson, Jason H. (Journal of Law and Commerce, 2013)
State Oversight of Nonprofit Governance: Confronting the Challenge of Mission Adherence Within a Multi-dimensional Standard